2017
DOI: 10.15406/hij.2017.01.00005
|View full text |Cite
|
Sign up to set email alerts
|

Potato Sprout Inhibition and Tuber Quality after Post-Harvest Treatment with Rosemary (Rosmarinus Officinalis L.) Leaves and Branches

Abstract: Storage of potatoes is one of the most important concerns in maintaining freshness and nutritional quality in the storage process. To achieve this, an experiment was carried out with five different storage conditions at various temperatures using fresh rosemary leaves and branches with three replicates. The results revealed that storage of potatoes at 25°C with rosemary leaves and branches resulted in the lowest sprout development and weight loss after 10 weeks. This was significantly different from either 4°C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 31 publications
(24 reference statements)
0
7
0
Order By: Relevance
“…The recommended gamma irradiation dose for sprout suppression varies from 40 ... 50 Gy to 120 ... 150 Gy [43][44][45][46][47]. The dose sufficient for sprout inhibition is apparently cultivar specific.…”
Section: Inhibiting Effect Of High Gamma Irradiation Dosesmentioning
confidence: 99%
See 4 more Smart Citations
“…The recommended gamma irradiation dose for sprout suppression varies from 40 ... 50 Gy to 120 ... 150 Gy [43][44][45][46][47]. The dose sufficient for sprout inhibition is apparently cultivar specific.…”
Section: Inhibiting Effect Of High Gamma Irradiation Dosesmentioning
confidence: 99%
“…Dhali et al [47] showed that 150 Gy 15 DAH resulted in less sugar accumulation during 2 months of storage rather than treatment 30 DAH. Rezaee et al [45] demonstrated that the later the treatment (10, 30 and 50 DAH were compared), the more sugar is accumulated after 5 months of storage both at +8 °С and +16 °С. After 120 days of storage tubers irradiated 5 DAH contained less reducing sugars than that 30 DAH [50].…”
Section: экономика и развитие агропромышленного комплекса в странах есmentioning
confidence: 99%
See 3 more Smart Citations